Green synthesis of Kickxia elatine-induced silver nanoparticles and their role as anti-acetylcholinesterase in the treatment of Alzheimer’s disease - Huda Noor Ul; Ghneim Hazem K.; Fozia Fozia; Ahmed Mushtaq; Mushtaq Nadia; Sher Naila; Khan Rahmat Ali; Ahmad Ijaz; Al-Sheikh Yazeed A.; Giesy John P.; Aboul-Soud Mourad A. M. (Green Processing and Synthesis, 2023)
The synthesis of silver nanoparticles (AgNPs) by the green method is favored as compared to chemical synthesis due to their appreciable properties of less toxicity and simple synthesis. The current study designed the biosynthesis of AgNPs in one step by using the plant Kickxia elatine (KE) extract and then investigated its inhibiting activity against rat’s brain acetylcholinesterase (AChE) ex vivo. Ultraviolet spectrum at 416 nm confirmed the formation of AgNPs. X-ray diffractometer calculated size was reported to be 42.47 nm. The SEM analysis confirmed spherical-shaped AgNPs. FT-IR suggested that the phytochemical groups present in the KE extract and their nanoparticles (NPs) are responsible for the biosynthesized of NPs. EDX analysis presented that Ag was the chief element with 61.67%. Both KE extract and AgNPs showed significant anti-AChE activity at 175 µg·mL−1. Statistical analysis showed that both KE and AgNPs exhibited non-competitive type inhibition against AChE, i.e. V max decreased (34.17–68.64% and 22.29–62.10%), while K m values remained constant. It is concluded that KE and AgNPs can be considered an inhibitor of rats’ brain AChE. Furthermore, the synthesis of AgNP-based drugs can be used as a cheaper and alternative option against diseases such as Alzheimer’s disease.